The Effectiveness of Yoga in Reducing Dysmenorrhea Pain in Adolescent Girls - Siregar, Amelia Erawaty; Rezeki, Sri; Siregar, Erin Padilla (Open Access Health Scientific Journal, 2025)
Background: In Indonesia, primary dysmenorrhea reaches 72.89%. The severity of dysmenorrhea in adolescent girls occurs in various levels, ranging from mild, moderate, to severe. There are various factors that play a role in influencing the severity of dysmenorrhea, including age, nutritional status, age at first menstruation, age of mother's menstruation, experience of pain at first menstruation, menstrual cycle, duration of menstruation, physical condition before menstruation, frequency of dysmenorrhea, duration of dysmenorrhea.Methods: This research design uses one group pretest-posttest design. Research conducted in Desa Bangun Rejo. The population in this study were female adolescents who experienced primary dysmenorrhea. This study used non-probability sampling with consecutive sampling by distributing questionnaires to see the scale of dysmenorrhea pain to be taken as a sample with the number of samples based on inclusion and exclusion criteria. The sample obtained was 30 respondents with a moderate pain scale. The research instrument used a dysmenorrhea questionnaire sheet with a measurement scale NRS (Numeric Rating Scale). Data analysis using non-parametric statistics Wilcoxon test to determine the effect of yoga movements in reducing dysmenorrhea in adolescent girls.Results: Research conducted on 30 respondents showed that Dysmenorrhea before doing yoga with an average score of 1.37 with the lowest score of 0 and the highest score of 2. The results of the study conducted on 30 respondents showed that Dysmenorrhea after doing yoga (Post test) with an average score (Mean) of 0.63 while the lowest score was at a score of 0 and the highest score was at a score of 2. The results of the bivariate analysis test were obtained by conducting a statistical test of the Wilcoxon Test and obtained significant results p-value = 0.000 (p <0.05).Conclusion: There was a significant difference in Dysmenorrhea before and after being given gymnastics treatment, so it can be concluded that there is the effectiveness of yoga gymnastics in reducing dysmenorrhea pain in adolescent girls.